News now : visual storytelling in the digital age - Green, Susan C., ....-; Lodato, Mark J., ....-; Schwalbe, Carol B., ....- (Boston (Mass.) : Pearson education, 2012)
Debuting in its first edition News Now: Visual Storytelling in the Digital Age helps today's broadcast journalism students prepare for a mobile, interactive, and highly competitive workplace. The authors, all faculty members of the prestigious Cronkite School of Journalism and Mass Communication, bring their real-world expertise to a book designed to be a trusted reference for the next generation of broadcast journalists.
Includes bibliographical references (p. 287) and indexes.
Keywords: Broadcast journalism; Online journalism; Digitale journalistiek